The relationship between amphetamine use, crime and psychiatric disorder among prisoners in New South Wales. - Riddell, S.; Nielssen, O.; Butler, Tony; MacDonald, C.; Starmer, G. (Australian and New Zealand Association of Psychiatry, Psychology and Law, 2006)
The study used data from a survey of the mental health of prisoners to examine possible links between amphetamine use, psychiatric disorder and the alleged offences for which the inmate was received to NSW prisons. Ethical approval was obtained to examine data from inmates received to NSW prisons in 2001. Prisoners had been interviewed using the CIDI-auto and several other structured questionnaires, using methodology similar to the National Mental Health Survey. Data analysis was carried out in the form of chi-square frequency tables and logistic regression. About a third of the inmates received to NSW prisons during the study period had been using amphetamines in the 12-month period before their arrest. The charges were more likely to be for robbery or property crimes (χ2 = 22.185, p = .014). Amphetamine users had more admissions to psychiatric hospitals (χ2 = 13.740, p < .001) than non-users and were more likely to report symptoms of psychotic illness (χ2 = 16.252, p < .001). The combination of amphetamine use and the reported presence of psychotic symptoms was associated with violent offending (OR = 1.86, p = .017). The results show that the charges laid against amphetamine users were similar to those for heroin users, but they suffered more psychiatric disorder. Those reporting psychotic symptoms were more likely to have allegedly committed violent offences.